An open algorithm to pre-process free text self-reported medications data in UK biobank - Xie, J; Hong, S; Delmestri, A; Khalid, S; Strauss, VY; Collins, G; Prieto-Alhambra, D (Wiley, 2022)
Introduction:UK Biobank is a large-scale biomedical research database with in-depth genetic and phenotypic information. However, baseline medication data are recorded as free text with semantic ambiguity and errors, potentially limiting their use for research.